2010
DOI: 10.5194/acp-10-2393-2010
|View full text |Cite
|
Sign up to set email alerts
|

Observations of OM/OC and specific attenuation coefficients (SAC) in ambient fine PM at a rural site in central Ontario, Canada

Abstract: Abstract. Ambient particulate matter (PM) samples were collected on quartz filters at a rural site in central Ontario during an intensive study in 2007. The concentrations of organic carbon (OC), pyrolysis organic carbon (POC), and elemental carbon (EC) were determined by thermal analysis. The concentrations are compared to the organic aerosol mass concentration (OM) measured with an Aerodyne C-ToF Aerosol Mass Spectrometer (AMS) and to the particle absorption coefficient (b asp ) obtained from a Radiance Rese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 96 publications
5
62
0
1
Order By: Relevance
“…According to studies, the calculated (OC/EC) min in spring, summer, autumn and winter was 1.34, 1.30, 0.91 and 1.03, respectively. Coef SOA/SOC was 1.4 in our study [23][24][25][26].…”
Section: Calculation Of Soas From Vocsmentioning
confidence: 86%
See 1 more Smart Citation
“…According to studies, the calculated (OC/EC) min in spring, summer, autumn and winter was 1.34, 1.30, 0.91 and 1.03, respectively. Coef SOA/SOC was 1.4 in our study [23][24][25][26].…”
Section: Calculation Of Soas From Vocsmentioning
confidence: 86%
“…In the present study, OC and EC concentrations obtained from online (4) In Equation (4), TOC is the total organic carbon content of fine particles in the atmosphere; EC is the elemental carbon content in fine particles; (OC/EC) min is the measured minimum ratio of OC/EC; and Coef SOA/SOC is the conversion factor between SOAs and SOCs [24]. According to studies, the calculated (OC/EC) min in spring, summer, autumn and winter was 1.34, 1.30, 0.91 and 1.03, respectively.…”
Section: Calculation Of Soas From Vocsmentioning
confidence: 99%
“…Results from Chan et al (2010) for Egbert 2007 found that the ratio of elemental carbon to organic matter (EC/OM) for the study was 0.2 except for the final Biogenic periods, during which it decreased to 0.15. Case 9 considers the normal case in which the ratio is 0.2 and the extra EC mass is assumed to be non-hygroscopic with a density of 1800 kg m −3 .…”
Section: Uncertaintiesmentioning
confidence: 99%
“…The overall goal of Egbert 2007 was to improve our understanding of the sources and hygroscopicity of organic aerosols. To this end, recent publications from this campaign have shown that the oxidation state of the aerosol correlates with the photochemical age of the air ), significant secondary organic aerosol (SOA) mass can be formed from monoterpene oxidation , oxygenated organic aerosols from anthropogenicallyinfluenced air could have primary and secondary sources, while biogenically-influenced air only had secondary sources (Chan et al, 2010), and aerosols from anthropogenicallyinfluenced air showed a delay in cloud droplet activation compared to biogenically-influenced air . The present study focuses on the hygroscopicity of the organic component of the aerosol by performing an aerosol-CCN closure experiment alongside measurements of the organic component of the gas and particulate phases, so as to best define the source of air sampled at CARE.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Turpin and Lim 41 concluded that a factor of about 1.6 would be appropriate for an urban organic aerosol, whereas a factor of 2.1 may be more appropriate for an aged, nonurban aerosol.…”
Section: Comparison Of Reconstructed To Measured Massmentioning
confidence: 99%